Linking pollutant exposure of humpback whales breeding in the Indian Ocean to their feeding habits and feeding areas off Antarctica. (January 2017) - Das, Krishna; Malarvannan, Govindan; Dirtu, Alin; Dulau, Violaine; Dumont, Magali; Lepoint, Gilles; Mongin, Philippe; Covaci, Adrian
Abstract: Humpback whales, Megaptera novaeangliae, breeding off la Reunion Island (Indian Ocean) undergo large-scale seasonal migrations between summer feeding grounds near Antarctica and their reproductive winter grounds in the Indian Ocean. The main scope of the current study was to investigate chemical exposure of humpback whales breeding in the Indian Ocean by providing the first published data on this breeding stock concerning persistent organic pollutants (POPs), namely polychlorinated biphenyls (PCBs), hexachlorobenzene (HCB), hexachlorocyclohexanes (HCHs), DDT and its metabolites (DDTs), chlordane compounds (CHLs), polybrominated diphenyl ethers (PBDEs), and methoxylated PBDEs (MeO-PBDEs). Analyses of stable isotopes δ 13 C and δ 15 N in skin resulted in further insight in their feeding ecology, which was in agreement with a diet focused mainly on low trophic level prey species, such as krill from Antarctica. POPs were measured in all humpback whales in the order of HCB > DDTs > CHLs > HCHs > PCBs > PBDEs > MeO-BDEs. HCB (median: 24 ng g −1  lw) and DDTs (median: 7.7 ng g −1  lw) were the predominant compounds in all whale biopsies. Among DDT compounds, p, p ′-DDE was the major organohalogenated pollutant, reflecting its long-term accumulation in humpback whales. Significantly lower concentrations of HCB and DDTs were found in females than in males (p < 0.001). Other compounds were similar between the two genders (p > 0.05). Differences in the HCB and DDTs suggested gender-specific transfer of some compounds to the offspring. POP concentrations were lower than previously reported results for humpback whales sampled near the Antarctic Peninsula, suggesting potential influence of their nutritional status and may indicate different exposures of the whales according to their feeding zones. Further investigations are required to assess exposure of southern humpback whales throughout their feeding zones. Graphical abstract: Highlights: POPs were measured in blubber of humpback whales breeding in the Indian Ocean. HCB, DDTs and CHLs were the predominant compounds in blubber samples. POP levels reflected low exposure of humpback whales from Indian Ocean. δ 13 C and δ 15 N values in skin reflected their diet in Antarctica focused on krill. Large variations of POP concentrations are apparent in Southern hemisphere whales. Abstract : Levels of POPs in humpback whales breeding in the Indian Ocean indicated low exposure.